The Mycobacterium avium complex. - Inderlied, C B (1993)
Mycobacterium avium complex (MAC) disease emerged early in the epidemic of AIDS as one of the common opportunistic infections afflicting human immunodeficiency virus-infected patients. However, only over the past few years has a consensus developed about its significance to the morbidity and mortality of AIDS. M. avium was well known to mycobacteriologists decades before AIDS, and the MAC was known to cause disease, albeit uncommon, in humans and animals. The early interest in the MAC provided a basis for an explosion of studies over the past 10 years largely in response to the role of the MAC in AIDS opportunistic infection. Molecular techniques have been applied to the epidemiology of MAC disease as well as to a better understanding of the genetics of antimicrobial resistance. The interaction of the MAC with the immune system is complex, and putative MAC virulence factors appear to have a direct effect on the components of cellular immunity, including the regulation of cytokine expression and function. There now is compelling evidence that disseminated MAC disease in humans contributes to both a decrease in the quality of life and survival. Disseminated disease most commonly develops late in the course of AIDS as the CD4 cells are depleted below a critical threshold, but new therapies for prophylaxis and treatment offer considerable promise. These new therapeutic modalities are likely to be useful in the treatment of other forms of MAC disease in patients without AIDS. The laboratory diagnosis of MAC disease has focused on the detection of mycobacteria in the blood and tissues, and although the existing methods are largely adequate, there is need for improvement. Indeed, the successful treatment of MAC disease clearly will require an early and rapid detection of the MAC in clinical specimens long before the establishment of the characteristic overwhelming infection of bone marrow, liver, spleen, and other tissue. Also, a standard method of susceptibility testing is of increasing interest and importance as new effective antimicrobial agents are identified and evaluated. Antimicrobial resistance has already emerged as an important problem, and methods for circumventing resistance that use combination therapies are now being studied.